Proposed content in health instruction for the first year high school - Panlilio, Teresita S. 1927- (s.n.], 1968)
The study proposed the content in health instruction for first year high school students based on the students' health needs and interests and the community health needs as drawn from local research studies and other documented resources. The proposed content in health instruction which consists of varied health areas have been consolidated under the central theme, "Understanding Your Health Needs."